Optimizing the Implementation of Total Quality Management at Yamaha Flagship Shop Bandung - Dedi Hadian; Aan Hardiyana; Senen Machmud; Maulana Yusup; Anton Tirta Komara; Bulan Tati Fitria; Robbi Saepul Rahman; Kuswanto Kuswanto; Muhamad Naufal Maulana Ashari; R. Yaka Novizak Kusumah; Rizal Abdul Azis Sudjatmiko (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2026)
The implementation of this community service project stems from quality improvement issues at the Yamaha Flagship Shop Bandung. Implementing Total Quality Management (TQM) can resolve these specific quality challenges. To investigate this, a team of lecturers and students conducts field research as the primary methodological approach. An optimal TQM framework maintains consistent service and product quality through strict, customer-oriented standardization. Therefore, the team optimizes TQM by focusing on service standardization through digitalization, human resource competency (employee involvement), product/spare part and repair quality control, customer-satisfaction supporting facilities (customer focus), and continuous improvement to successfully elevate the overall service quality at the Yamaha Flagship Shop Bandung.